ANALISIS IDIOSINKRATIK PUTRA MAHKOTA MUHAMMAD BIN SALMAN ATAS KEBIJAKAN SAUDI VISION 2030 - Mutiara Ayu, Femmyoroi; Putri, Penny Kurnia; Parameswari, Anak Agung Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 02 (2022): Jurnal DIKSHI, 2022)
This study aims to explain the reasons for Muhammad bin Salman (MBS) in making the Saudi Vision 2030 policy, which was analyzed based on the idiosyncratic aspect. So far, Saudi Arabia has depended its main economic source on oil. With the decline in world oil prices in 2015, MBS believes that by turning the main source of Saudi Arabia's economy into tourism through the Saudi Vision 2030 policy, it will make Saudi Arabia's economy stable in the future. The research was conducted in an explanatory qualitative manner, with the Idiosyncratic Model framework in foreign policy analysis. This study found that MBS's background as the eldest son of the royal family gave him a great opportunity to become a leader. His ambition towards Saudi Vision 2030 made him fall into the category of leaders who have a style and type of leadership that is Goal Oriented and Strategic Charismatic.   Keywords: Crown Prince Muhammad Bin Salman, Idiosyncratic, Leader’s Personality, Saudi Vision 2030,